1997
DOI: 10.1071/mf96090
|View full text |Cite
|
Sign up to set email alerts
|

Flood-mediated changes in aquatic macrophyte community structure

Abstract: Sixteen artificial billabongs on the floodplain of the River Murray, New South Wales, were surveyed over a 14-month period to observe the effect of different hydrological regimes on the development of aquatic macrophyte communities. The billabongs were initially planted with Vallisneria sp. and Myriophyllum papillosum Orch. in November 1994, then flooded. The 16 billabongs were divided into four treatments: summer flood, spring flood, permanent inundation, and a control treatment that was initially flooded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 0 publications
1
32
0
1
Order By: Relevance
“…During the course of the experiment a further 12 plant taxa colonized the experimental billabongs (Nielsen and Chick, 1997).…”
Section: Experimental Designmentioning
confidence: 99%
“…During the course of the experiment a further 12 plant taxa colonized the experimental billabongs (Nielsen and Chick, 1997).…”
Section: Experimental Designmentioning
confidence: 99%
“…In fact, they have never before been researched. Floodplain plant communities are known to respond to the frequency, duration, timing, and depth of flooding as well as the period between flood events (Nielsen and Chick 1997;Blanch et al 1999;Casanova and Brock 2000;Robertson et al 2001;Greet et al 2011), such that species can assemble into response guilds characterized by their adaptations to tolerate or avoid flooding (Merritt et al 2010). Flood-related factors may vary based on the manner by which wetlands are connected to the river.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Hamabata and Kobayashi (2002) and McGowan et al (2005) recorded increases in macrophyte growth following declines in water level, although Nicol and Ganf (2000) found that in outdoor ponds some species of aquatic macrophytes survive water declines better than others. Water level fluctuations have been correlated with net annual primary production (Medeiros dos Santos and de Assis Esteves, 2002) and may influence macrophyte communities by changing species composition (Walker et al, 1994;Nielsen and Chick, 1997;Blanch et al, 1999;Blanch et al, 2000;Riis and Hawes, 2002) and reducing macrophyte abundance (Harwell and Havens, 2003). Flow-on effects to animals dependent on macrophytes have also been reported (Humphries, 1996;Richardson et al, 2002).…”
Section: Introductionmentioning
confidence: 91%